Study of Seroprevalence of HIV, HBV, HCV and Syphilis among Blood Donors at Tertiary Care Hospital in North Karnataka - Sanjay Venkatrao Khandekar; Shashidhar Fakirappa Chulki (Medsci Publications, 2018)
Background: Transfusion transmissible infections (TTIs) such as Human Immunodeficiency Virus (HIV), Hepatitis B Virus (HBV), Hepatitis C Virus (HCV) and Syphilis are among the greatest threats to blood safety for the recipient. So the present study was conducted to know the prevalence and trends of TTIs. Methods: The present study was carried out at the Blood bank at- tached to Bidar Institute of Medical Sciences Bidar. In this study donors who donated blood at blood bank during five year period were retrospectively evaluated with respect to HBV, HCV, HIV, Syphilis seroprevalance. Results: During the five year period of study there was increase in the blood donors and decrease in the seroprevalence of transfusion transmitted transfusions. Out of 26056 blood donors, 847 had sero- logical evidence of infection. The overall seroprevalence was 3.25%. The seroprevalence was high for HBV i.e. 2.88%, followed by 0.28% for HIV, 0.04% for HCV and 0.03% for VDRL. Conclusion: In present study there was year wise increase in the blood donations at the same time there was year wise decrease in the seroprevalence of transfusion transmitted infections. The most common transfusion transmitted infection was Hepatitis B fol- lowed by HIV then HCV and last Syphilis. The seroprevalence of transfusion transmitted infection should be decreased further.